Rural Consumers’ Financial Literacy and Access to FinTech Services - Mohammad Abedin (Journal of the Knowledge Economy, 2023)
The study aims to show the impact of financial knowledge among rural consumers’ access to financial technology services. In general, knowledge regarding any particular fact helps consumers to select or reject different options. Therefore, knowledge regarding financial services is considered a factor that influences access to financial technology services. This study carries out a survey-oriented method with a structured questionnaire. According to the data category, this study uses three well-known econometric models: logistic regression, probit regression, and complementary log–log regression, have been experimented. This study finds that knowledge regarding various factors significantly impact on access to financial technology services. Mainly, this study has important practical significance for the use of rural finance and financial technology in rural areas, which affects the entire economy.